Adverse birth outcomes associated with Zika virus exposure during pregnancy in Sao Jose do Rio Preto, Brazil - Nogueira, M. L.; Nery Junior, N. R. R.; Estofolete, C. F.; Bernardes Terzian, A. C.; Guimaraes, G. F.; Zini, N.; Alves da Silva, R.; Dutra Silva, G. C.; Junqueira Franco, L. C.; Rahal, P. [UNESP]; Bittar, C. [UNESP]; Carneiro, B. [UNESP]; et al. (Elsevier B.V., 2018)
Objectives: We aimed to report the first 54 cases of pregnant women infected by Zika virus (ZIKV) and their virologic and clinical outcomes, as well as their newborns' outcomes, in 2016, after the emergence of ZIKV in dengue-endemic areas of Sao Paulo, Brazil. Methods: This descriptive study was performed from February to October 2016 on 54 quantitative realtime PCR ZIKV-positive pregnant women identified by the public health authority of Sao Jose do Rio Preto, Sao Paulo, Brazil. The women were followed and had clinical and epidemiologic data collected before and after birth. Adverse outcomes in newborns were analysed and reported. Urine or blood samples from newborns were collected to identify ZIKV infection by reverse transcription PCR (RT-PCR). Results: A total of 216 acute Zika-suspected pregnant women were identified, and 54 had the diagnosis confirmed by RT-PCR. None of the 54 women miscarried. Among the 54 newborns, 15 exhibited adverse outcomes at birth. The highest number of ZIKV infections occurred during the second and third trimesters. No cases of microcephaly were reported, though a broad clinical spectrum of outcomes, including lenticulostriate vasculopathy, subependymal cysts, and auditory and ophthalmologic disorders, were identified. ZIKV RNA was detected in 18 of 51 newborns tested and in eight of 15 newborns with adverse outcomes. Conclusions: Although other studies have associated many newborn outcomes to ZIKV infection during pregnancy, these same adverse outcomes were rare or nonexistent in this study. The clinical presentation the newborns we studied was mild compared to other reports, suggesting that there is significant heterogeneity in congenital Zika infection. (C) 2017 European Society of Clinical Microbiology and Infectious Diseases. Published by Elsevier Ltd. All rights reserved.
Keywords: Adverse outcome; Arbovirus; Birth; Pregnancy; Zika virus